Enhancing Early Childhood Education: Boosting Educator Skills through Collaboration between PAUD Working Group and Higher Education Institutions - Diding Nurdin; Gema Muhammad Shidiq (AL-ISHLAH: Jurnal Pendidikan, 2024)
This research investigates the development and implementation of a cooperative strategy to enhance educational competence in early childhood education through collaboration between Early Childhood Education Groups (PAUD) and higher education institutions. Employing a qualitative case study approach, the study was conducted at the Pokja Bunda Secretariat in West Java. Purposive sampling was used to select relevant individuals and locations to explore the collaboration between the Bunda PAUD Working Group in West Java Province and universities aimed at improving educators' competencies in early childhood education. Data collection methods included observations, interviews, document studies, and analysis of audiovisual materials. The findings revealed that a collaborative strategy utilizing the Penta helix framework, particularly in Bandung City, effectively enhances educators' competencies. This was achieved through various collaborative activities involving International Women University, Indonesian Education University, Bandung Islamic University, SEAMEO CECCEP, CIMB Niaga Bank, and the West Java Provincial Office of Education.